Tension Pneumatocele a Rare Presentation - Aftabuddin, Md; Rahman, Md Mokhlesur; Khan, Omar Sadeque; Adhikary, Asit Baran (Medicine Today, 2016)
A 10 months old female baby admitted with diagnosis of tension pneumatocele in right side of hemithorax with collapse right lung. The baby was first managed conservatively, but the condition did not improve. Surgical management was done after one month of admission in hospital, with improvement of baby's symptoms and general conditions. One month later the baby was well and her lung was found expanded completely. Medicine Today 2015 Vol.27(2): 37-39